Semantic Bootstrapping: A Theoretical Perspective - Wu, Wentao; Li, Hongsong; Wang, Haixun; Zhu, Kenny Q. (IEEE Transactions on Knowledge and Data Engineering (TKDE), 2017)
Knowledge acquisition is an iterative process. Most previous work has focused on bootstrapping techniques based on syntactic patterns, that is, each iteration finds more syntactic patterns for subsequent extraction. However, syntactic bootstrapping is incapable of resolving the inherent ambiguities in the syntactic patterns. The precision of the extracted results is thus often poor. On the other hand, semantic bootstrapping bootstraps directly on knowledge rather than on syntactic patterns, that is, it uses existing knowledge to understand the text and acquire more knowledge. It has been shown that semantic bootstrapping can achieve superb precision while retaining good recall. Nonetheless, the working mechanism of semantic bootstrapping remains elusive. In this paper, we present a detailed analysis of semantic bootstrapping from a theoretical perspective. We show that the efficiency and effectiveness of semantic bootstrapping can be theoretically guaranteed. Our experimental evaluation results substantiate the theoretical analysis.